Ab initio phase diagram of silver. (21st September 2021) - Baty, S R; Burakovsky, L; Errandonea, D
Abstract: Silver has been considered as one of the simple one-phase materials that do not exhibit high pressure or high temperature polymorphism. The solid phase of Ag at ambient conditions is face-centered cubic (fcc) one. However, very recently another solid phase of silver, body-centered cubic (bcc) one, was detected in shock-wave (SW) experiments, and a more sophisticated phase diagram of Ag with the two solid phases was published by Smirnov. In this work, using a suite of ab initio quantum molecular dynamics (QMD) simulations based on the Z methodology which combines both direct Z method for the simulation of melting curves and inverse Z method for the calculation of solid–solid phase boundaries, we refine the phase diagram of Smirnov. We calculate the melting curves of both fcc-Ag and bcc-Ag and obtain an equation for the fcc–bcc solid–solid phase transition boundary. We also obtain the thermal equation of state of Ag which is in agreement with experimental data and QMD simulations. We argue that, despite being a polymorphic rather than a simple one-phase material, silver can be considered as an SW standard.